2017
DOI: 10.7556/jaoa.2017.006
|View full text |Cite
|
Sign up to set email alerts
|

Osteopathic Philosophy and Manipulation Enhancement Program: Influence on Osteopathic Medical Students’ Interest in Osteopathic Manipulative Medicine

Abstract: The OPME program improved students' interest in OMM and can be modified and implemented in any college of osteopathic medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
(15 reference statements)
0
5
1
Order By: Relevance
“…Contrary to numerous published studies stating that the overall usage of OMM/OMT among all DOs is decreasing, 2,3,9,10,11,12,13,14,34 respondents in this study were found to practice OMM often, and the greatest number of AAO members utilizing OMM/OMT had completed residencies within the last 5 years (96 [21.9%]).…”
Section: (Continued On Page 20) (Continued From Page 18)contrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to numerous published studies stating that the overall usage of OMM/OMT among all DOs is decreasing, 2,3,9,10,11,12,13,14,34 respondents in this study were found to practice OMM often, and the greatest number of AAO members utilizing OMM/OMT had completed residencies within the last 5 years (96 [21.9%]).…”
Section: (Continued On Page 20) (Continued From Page 18)contrasting
confidence: 99%
“…22,23 The interest in OMM and OMT wanes after the first 2 years of medical school, and the use of OMT is declining among osteopathic residents and physicians. 2,3,9,10,11,12,13,14,24 This is true in spite of an increase in the number of colleges of osteopathic medicine (COM). 13 Ching expounded upon this by discussing osteopathic postgraduate training by stating many DOs used to complete a traditional rotating internship and then enter into practice.…”
Section: Osteopathic Recognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported correlation between increased exposure to OMT and higher levels of agreement with osteopathic philosophy statements and intention to use OMT. 7,8 It also has been proposed that clinical exposure to OMT during the didactic years is an effective way to encourage students to later use OMT clinically. [7][8][9] This survey yielded similar findings, with a significantly higher proportion of respondents strongly agreeing with statements about clinical utility of OMT as well as intention to use OMT in future practice among students who had received OMT from OMM fellows (Table 2).…”
Section: Discussionmentioning
confidence: 99%